The Development of Peace Counseling Model (PCM): Strategy of School Counselor to Reduce Students’ Aggressive Behavior - Saputra, Wahyu Nanda Eka; Ayriza, Yulia; Handaka, Irvan Budhi; Ediyanto, Ediyanto (Jurnal Kajian Bimbingan dan Konseling, 2019)
This study aimed to develop a counseling model to reduce students’ aggressive behavior, namely Peace Counseling Model (PCM). This counseling model uses the basic theory of peace education that is specifically implemented in counseling. This study adapted the research and development model formulated by Borg & Gall. The research used quantitative descriptive analysis. There was a strong agreement between experts and practitioners on the feasibility of the product being developed to be implemented by school counselor. The results of this study should be a reference to further research to test the effectiveness of PCM to reduce students’ aggressive behavior.